Tactical and technical performance analysis of the male 65 kg category at the Brazilian shotokan karate championship - Ribas, R. M.; Pereira, M. A. S.; Barbosa, T. A.; Lass, A. D.; Bassan, J. C. (Journal of Physical Education, 2020)
The aim of the present study was to identify the most used techniques by medalists and defeated athletes during the Brazilian Shotokan Karate Championship of 2017. Eleven fights involving thirteen athletes (28.5±3.7yrs.) who competed in the category "up to 65 Kg 1st KYU" were investigated. Analysis were conducted by six specialists through the observation and register technique using the tactical and technical spreadsheet Scout Karate. The Anova test was used to compare actions and techniques mostly used. The Chi-square test for independent samples was used to verify the existence of significant differences among the techniques used by the winning and defeated athletes (p<0.05). Results show that the most frequent attack during fights was the "Mawashi geri", 26.3±1.5 times, followed by "Gyaku zuki" with 19.5±2.0 times (p<0.01). The most visualized tactical action during combats was the attack with 47.5±5.5 times (p<0.01). "Mawashi geri" was the mostly used attack (p=0.01) performed by winners (71.4%) when compared with the defeated athletes (28.6%). The results indicate that the "Mawashi geri" attack was the most assertive decision used in the category "up to 65 Kg 1st KYU".